Rezim Kebenaran Rasionalisme dalam Diskursus Kegilaan dan Tindakan Pendisiplinan Pasung sebagai Kejahatan - Albert Wirya (Jurnal Kriminologi Indonesia, 2013)
The life condition of people who are identified as “mad” in society intensely depend upon the development of discourse of madness. In Indonesia, the discourses of madness cause many families to commit confinement (pasung) upon their own family member. The discourses of madness, which limit the movement of a person during many years, are created by the combination of power and knowledge in social structure thus creating a regime of truth. The constitutive criminology theory is used to analyze the regime of truth in madness discourses that harm the life of two confinement (pasung) subjects in Indonesia. This research shows that discourses of madness, which carry rationalism regime of truth and cause body discipline on ‘mad’ people, are a crime that has to be resolved by replacement discourses. Human agencies can build together a replacement discourse using the chaos theory and existentialism psychology